Correlates of co-occurring eating disorders and substance use disorders: a case for dialectical behavior therapy. Issue 2 (3rd March 2020) - Claudat, Kimberly; Brown, Tiffany A.; Anderson, Leslie; Bongiorno, Gina; Berner, Laura A.; Reilly, Erin; Luo, Tana; Orloff, Natalia; Kaye, Walter H.
ABSTRACT: Given the high rates of comorbidity between eating disorders (EDs) and substance use disorders (SUDs), it is important to develop effective treatment approaches for individuals with both an ED and SUD (ED-SUD). To date, there is limited information guiding the concurrent treatment of these disorders. To build on existing research, the present study compared adult patients with ED-SUD ( n = 36) to patients with ED-only ( n = 62) in terms of demographics, psychiatric comorbidity, and self-reported eating disorder and related psychopathology. Results indicated that ED-SUD patients had a higher number of psychiatric comorbidities, were more likely to be prescribed mood stabilizers, and were more sensitive to reward. They also reported greater difficulty with emotion regulation, including more difficulty engaging in goal-directed activity, higher impulsivity, and more limited access to emotion regulation strategies. These differences highlight the importance of targeting emotion dysregulation for ED-SUD, and provide evidence for the importance of integrated, transdiagnostic treatment to simultaneously address the SUD, ED, and other psychiatric comorbidities. Implications for tailoring treatment are discussed with a focus on Dialectical Behavior Therapy (DBT).